The Chinese Economy, Past, Present and Future - Claus, I.; Oxley, Leslie (2015)
China's rapid economic growth and development was reinforced by industrialization, mainly driven by export-oriented and labor-intensive industries in Eastern China's coastal cities, and urbanization. China's industrialization has also occurred in an economy with a relatively low level and growth rate of informatization and the extent to which China is becoming information based lags behind other countries. This chapter reviews nine up-to-date surveys that discusses some key aspects of the Chinese economy, past, present and future. They survey the present and future challenges of the Chinese economy, based upon a rich (ancient) past, yet contested (recent) history, and identify some common themes, such as the household registration system, urbanization, demographic transition, inequality and the sustainability of economic growth. China's economic growth over the past decades has been spurred largely by economies of scale in labor-intensive industries rather than through invention and innovation.